This angel on my chest : stories - Pietrzyk, Leslie, 1961- (Pitt Drue Heinz Lit Prize., 2015)
Winner of the 2015 Drue Heinz Literature Prize. Selected by Jill McCorkle. This Angel on My Chest is a collection of unconventionally linked stories, each about a different young woman whose husband dies suddenly and unexpectedly. Ranging from traditional stories to lists, a quiz, a YouTube link, and even a lecture about creative writing, the stories grasp to put into words the ways in which we all cope with unspeakable loss. Based on the author's own experience of losing her husband at age thirty-seven, this book explores the resulting grief, fury, and bewilderment, mirroring the obsessive nature of grieving. The stories examine the universal issues we face at a time of loss, as well as the specific concerns of a young widow: support groups, in-laws, insurance money, dating, and remarriage. This Angel on My Chest ultimately asks, how is it possible to move forward with life while "till death do you part" rings in your ears?and, how is it possible not to?